Evolution of Bacterial Communities, Physicochemical Changes and Sensorial Attributes of Natural Whole and Cracked Picual Table Olives During Spontaneous and Inoculated Fermentation - Anagnostopoulos, Dimitrios A.; Kamilari, Eleni; Tsaltas, Dimitrios (Frontiers in Microbiology, 2020)
Table olives are one of the most well-known traditionally fermented products and their global consumption is exponentially increasing. In directly brining, table olives are produced spontaneously, without any debittering pre-treatment. Up to date, fermentation process remains empirical and inconstant, as it is affected by the physicochemical attributes of the fruit, tree and fruit management of pro and post-harvest, influencing also the natural microbiota on olive drupes. In the present study, whole and cracked Picual table olives were fermented at industrial scale for 120 days, using three distinct methods (natural fermentation, inoculation with Lactic Acid Bacteria at a 7% or a 10% NaCl concentration). Microbial, physicochemical and sensorial alterations were monitored during whole process and several discrepancies were observed between treatments. Results indicated that in all treatments the dominant microflora were Lactic Acid Bacteria, while yeasts detected in noteworthy populations, especially in non-inoculated samples. LAB population in inoculated samples was significant higher. Microbial profiles detected by metagenomic approach, showed meaningful differences, between spontaneous and inoculated treatments. As a result, the profound dominance of starter culture had a severe effect on olives fermentation, resulting in lower pH and higher acidification, which was mainly caused by the higher levels of lactic acid produced. Furthermore, the elimination of Enterobacteriaceae was shortened, even at lower salt concentration. Although no effect was observed concerning the quantitated organoleptic parameters such as color and texture, significant higher levels in terms of antioxidant capacity were recorded in inoculated samples, while the degradation time of oleuropein was shortened, leading to the production of higher levels of hydroxytyrosol, as well. Based on those evidences, the establishment of starter culture driven Picual olives fermentation is strongly recommended. It is crucial to mention that the inoculated treatment with reducing sodium content was highly appreciated by the sensory panel, enhancing the hypothesis that the production of Picual table olives at reduced NaCl levels is achievable.